Spatial distributions of acoustic scattering groups during the warm-to-cold transition period in the Senegal coastal ecosystem and their relationships with environmental variables - Viviane David; Jérémie Habasque; Gildas Roudaut; Louis Marie; Delphine Thibault; Anne Lebourges-Dhaussy; Xavier Capet; Eric Machu (Journal of Marine Systems, 2025)

Variability of bottom dissolved oxygen on the southern Senegalese shelf at intraseasonal to interannual time scales using a modelling approach - Abdoul Wahab Tall; Vincent Echevin; Xavier Capet; Eric Machu (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Connecting flow–topography interactions, vorticity balance, baroclinic instability and transport in the Southern Ocean: the case of an idealized storm track - Julien Jouanno; Xavier Capet (Ocean Science, 2020)
The dynamical balance of the Antarctic Circumpolar Current and its implications on the functioning of the world ocean are not fully understood and poorly represented in global circulation models. In this study, the sensitivities of an idealized Southern Ocean (SO) storm track are explored with a set of eddy-rich numerical simulations. The classical partition between barotropic and baroclinic modes is sensitive to current–topography interactions in the mesoscale range 10–100 km, as comparisons between simulations with rough or smooth bathymetry reveal. Configurations with a rough bottom have weak barotropic motions, ubiquitous bottom form stress/pressure torque, no wind-driven gyre in the lee of topographic ridges, less efficient baroclinic turbulence and, thus, larger circumpolar transport rates. The difference in circumpolar transport produced by topographic roughness depends on the strength with which (external) thermohaline forcings by the rest of the world ocean constrain the stratification at the northern edge of the SO. The study highlights the need for a more comprehensive treatment of the Antarctic Circumpolar Current (ACC) interactions with the ocean floor, including realistic fields of bottom form stress and pressure torque. It also sheds some light on the behavior of idealized storm tracks recently modeled: (i) the saturation mechanism, whereby the circumpolar transport does not depend on wind intensity, is a robust and generic attribute of ACC-like circumpolar flows; (ii) the adjustment toward saturation can take place over widely different timescales (from months to years) depending on the possibility (or not) for barotropic Rossby waves to propagate signals of wind change and accelerate/decelerate SO wind-driven gyres. The real SO having both gyres and ACC saturation timescales typical of our “no gyre” simulations may be in an intermediate regime in which mesoscale topography away from major ridges provides partial and localized support for bottom form stress/pressure torque.

Weakening of the Senegalo–Mauritanian upwelling system under climate change - Adama Sylla; Juliette Mignot; Xavier Capet; Amadou Thierno Gaye (Climate Dynamics, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

A model perspective on the dynamics of the shadow zone of the eastern tropical North Atlantic – Part 1: the poleward slope currents along West Africa - Lala Kounta; Xavier Capet; Julien Jouanno; Nicolas Kolodziejczyk; Bamol Sow; Amadou Thierno Gaye (Ocean Science, 2018)
The West African seaboard is one of the upwelling sectors that has received the least attention, and in situ observations relevant to its dynamics are particularly scarce. The current system in this sector is not well known and understood, e.g., in terms of seasonal variability, across-shore structure, and forcing processes. This knowledge gap is addressed in two studies that analyze the mean seasonal cycle of an eddy-permitting numerical simulation of the tropical Atlantic. Part 1 is concerned with the circulation over the West African continental slope at the southernmost reach of the Canary Current system, between ∼8 and 20∘ N. The focus is on the depth range most directly implicated in the wind-driven circulation (offshore and coastal upwellings and Sverdrup transport) located above the potential density σt=26.7 kg m−3 in the model (approx. above 250 m of depth). In this sector and for this depth range, the flow is predominantly poleward as a direct consequence of positive wind stress curl forcing, but the degree to which the magnitude of the upper ocean poleward transport reflects Sverdrup theory varies with latitude. The model poleward flow also exhibits a marked semiannual cycle with transport maxima in spring and fall. Dynamical rationalizations of these characteristics are offered in terms of wind forcing of coastal trapped waves and Rossby wave dynamics. Remote forcing by seasonal fluctuations of coastal winds in the Gulf of Guinea plays an instrumental role in the fall intensification of the poleward flow. The spring intensification appears to be related to wind fluctuations taking place at shorter distances north of the Gulf of Guinea entrance and also locally. Rossby wave activity accompanying the semiannual fluctuations of the poleward flow in the coastal waveguide varies greatly with latitude, which in turn exerts a major influence on the vertical structure of the poleward flow. Although the realism of the model West African boundary currents is difficult to determine precisely, the present in-depth investigation provides a renewed framework for future observational programs in the region.

Eddy properties in the Southern California Current System - Fanny Chenillat; Peter J. S. Franks; Xavier Capet; Pascal Rivière; Nicolas Grima; Bruno Blanke; Vincent Combes (Ocean Dynamics, 2018)

Western boundary upwelling dynamics off Oman - Clément Vic; Xavier Capet; Guillaume Roullet; Xavier Carton (Ocean Dynamics, 2017)

Dissipation of the energy imparted by mid-latitude storms in the Southern Ocean - Julien Jouanno; Xavier Capet; Gurvan Madec; Guillaume Roullet; Patrice Klein (Ocean Science, 2016)
The aim of this study is to clarify the role of the Southern Ocean storms on interior mixing and meridional overturning circulation. A periodic and idealized numerical model has been designed to represent the key physical processes of a zonal portion of the Southern Ocean located between 70 and 40° S. It incorporates physical ingredients deemed essential for Southern Ocean functioning: rough topography, seasonally varying air–sea fluxes, and high-latitude storms with analytical form. The forcing strategy ensures that the time mean wind stress is the same between the different simulations, so the effect of the storms on the mean wind stress and resulting impacts on the Southern Ocean dynamics are not considered in this study. Level and distribution of mixing attributable to high-frequency winds are quantified and compared to those generated by eddy–topography interactions and dissipation of the balanced flow. Results suggest that (1) the synoptic atmospheric variability alone can generate the levels of mid-depth dissipation frequently observed in the Southern Ocean (10−10–10−9 W kg−1) and (2) the storms strengthen the overturning, primarily through enhanced mixing in the upper 300 m, whereas deeper mixing has a minor effect. The sensitivity of the results to horizontal resolution (20, 5, 2 and 1 km), vertical resolution and numerical choices is evaluated. Challenging issues concerning how numerical models are able to represent interior mixing forced by high-frequency winds are exposed and discussed, particularly in the context of the overturning circulation. Overall, submesoscale-permitting ocean modeling exhibits important delicacies owing to a lack of convergence of key components of its energetics even when reaching Δx = 1 km.

Heat balance and eddies in the Peru-Chile current system - François Colas; James C. McWilliams; Xavier Capet; Jaison Kurian (Climate Dynamics, 2012)

The influence of diel vertical migration on zooplankton transport and recruitment in an upwelling region: estimates from a coupled behavioral‐physical model - SARAH D. CARR; XAVIER J. CAPET; JAMES C. MCWILLIAMS; J. TIMOTHY PENNINGTON; FRANCISCO P. CHAVEZ (Fisheries Oceanography, 2008)
Diel vertical migration (DVM) is a common zooplankton behavior in which organisms reside in surface or near‐surface waters at night and at deeper depths during the day. In many upwelling regions, DVM reduces the transport of organisms away from the region. It is unclear, however, what role DVM plays in recruitment (the arrival of larvae or juveniles to locations where they will become reproducing adults) to upwelling regions. In this study, we estimate the influence of DVM on zooplankton transport, the level of recruitment of locally produced propagules (self‐recruitment), and sources of recruits in the upwelling region near Monterey Bay, California, by simulating the trajectories of fixed‐depth and vertically migrating organisms with a drifter‐tracking algorithm driven by climatological velocity fields from a three‐dimensional hydrodynamic model. Our simulations suggest that DVM into subsurface poleward and onshore currents during the day does not fully compensate for equatorward and offshore transport in the surface Ekman layer at night and does not retain zooplankton in the Monterey Bay region. Our simulations also suggest that DVM decreases the ability of zooplankton to return to the region after being transported away and shifts source regions for recruits closer to the bay. While DVM does not appear to substantially increase the potential for self‐recruitment to the region, this study indicates that other mechanisms, such as transport during non‐upwelling periods, continuous transport below the surface, increases in mean transport depth over time, or seasonal changes in hydrography, may still enable relatively high levels of self‐recruitment to this highly advective region.